Assessing Trust in AI-Driven Marketing: Factors, Implications, and Opportunities - Fazelian, Soudeh (Digital Repository of Theses, 2026)
This study investigates the factors influencing trust in AI-driven marketing in the cosmetic industry, analyzing the key elements that shape consumer perceptions and their implications for marketing strategies. The research aims to assess how various trust dimensions—such as reliability, privacy management, user control, adaptability, and functionality—impact consumer engagement and purchasing decisions in the context of AI-powered marketing efforts. A questionnaire comprising 16 dimensions and 55 items was administered to a sample of 176 customers from a well-known cosmetic company. The findings reveal significant insights into the role of trust in fostering consumer relationships with AI-driven marketing, highlighting the importance of transparency, reliability, and personalized experiences. Statistical analyses, including Cronbach's Alpha, KMO and Bartlett’s Test, One-Sample T-Test, and ANOVA as well as DEA were employed to validate the findings and assess the performance of trust factors. The study found that dimensions such as reliability, user control, and third-party recognition showed strong correlations with consumer trust, while privacy management and ethical considerations presented challenges in fostering trust. This research contributes to the understanding of how AI-driven marketing can be leveraged to build stronger consumer trust in the cosmetic industry, offering practical recommendations for enhancing marketing strategies and improving consumer engagement. The study also outlines future research directions to explore the long-term effects of AI on consumer behavior and the integration of AI with other emerging technologies. Keywords: AI-driven marketing, trust, cosmetic industry, consumer behavior, artificial intelligence, marketing strategies